Mini-symposium on Future Trends in Serious Games for Cultural Heritage - Paneva-Marinova, Desislava; Pavlov, Radoslav (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2018)
In combination with the appropriate content, serious games become an important modern-day educational tool, which reflects both the current state of technology and learners’ social profiles. The method helps instructors to motivate student learning, curiosity, creative and logical thought, as well as develop a variety of skills and competencies. Serious educational games aim to cultivate better comprehension strategies, creative thinking, learning-by-doing (production, authorship), and students’ engagement in their own cognition and learning processes. This mini-symposium on Future Trends in Serious Games for Cultural Heritage will present outcomes of the Serious Education Games as Contemporary Tools for New Educational Applications project, Contract DSD- 2/05.04.2017, between the Bulgarian Academy of Sciences and the Institute of Mathematics and Informatics, activity Introduction of Contemporary Methods in Educating and Fostering Young Talent (PMC No 347), other projects in the field and will outline some future trends for cultural heritage game development.